Following the footprints of SME competitiveness in a high-technology sector - Farinha, Luís (2020)
This chapter examines the competitiveness footprints of SMEs within a high-tech cluster. A mixed methodology combining quantitative and qualitative data is used. More specifically, a case study is offered to show trends in innovative and entrepreneurial collaboration associated with an internationally competitive high-tech cluster. The findings shed light on the importance of collective efficiency strategies, with a focus on RD&I, implemented by SMEs that operate in an international and competitive market. This chapter highlights the lessons learned in two specific aspects: the role of innovation in the competitiveness of SMEs and the role of innovation and entrepreneurship networks in enhancing the functions of a high-technology industrial cluster, the Portuguese Engineering and Tooling Cluster.